1998
DOI: 10.1038/sj.jhh.1000721
|View full text |Cite
|
Sign up to set email alerts
|

Is elevation of clinic blood pressure in patients with white coat hypertension who have normal ambulatory blood pressure associated with target organ changes?

Abstract: Background:The issue as to whether white coat hypertension is a pathologically significant entity, with associated target organ changes, or that the condition carries the same risk for target organ involvement as normotension, is undecided. Previous studies which have shown pathological correlates between white coat hypertension and target organ damage have not controlled for the most obvious confounder, mean 24 h blood pressure (BP). Methods and results: In this study we retrospectively identified 33 age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
(40 reference statements)
2
35
0
2
Order By: Relevance
“…Both observations are largely in agreement with a growing literature on these aspects of white coat hypertension, [5][6][7] but now reason deserts the authors in their hour of need. Having made their case they go on to make two recommendations with far-reaching implications: first, that subjects with white coat hypertension should have echocardiography, and, second, that they should have their clinic blood pressure measured by the traditional technique every 6 months.…”
supporting
confidence: 87%
“…Both observations are largely in agreement with a growing literature on these aspects of white coat hypertension, [5][6][7] but now reason deserts the authors in their hour of need. Having made their case they go on to make two recommendations with far-reaching implications: first, that subjects with white coat hypertension should have echocardiography, and, second, that they should have their clinic blood pressure measured by the traditional technique every 6 months.…”
supporting
confidence: 87%
“…Many, but not all, of these studies have demonstrated increased LVMI in WCH subjects, with LVMI intermediate between that of subjects with normotension and those with sustained hypertension. [2][3][4][5][6][7][8][9][10][11][12][13] In addition, a recent study suggests that the long-term incidence of stroke may be elevated in adults with WCH. 14 Little is known about the clinical significance and natural history of WCH in children.…”
mentioning
confidence: 99%
“…They found that the LVMI was significantly greater in patients with WCH than in controls, a difference which persisted even after secondary matching for 24-h BP, and in a multiple regression model, WCH was the only significant predictor of LVMI. In contrast to Hoegholm et al, 13 the data from Owens et al 11 suggests that changes in left ventricular structure are not entirely accounted for by the level of BP and that other features may distinguish the patient with WCH from the truly normotensive individual. WCH may therefore result in a degree of LVH, which is probably one of the more important indices of hypertensive target organ damage.…”
Section: Association With Target Organ Damagementioning
confidence: 80%
“…It is therefore impossible to distinguish a dose-dependent response to BP level from a true WCH effect. 11,12 For example, Verdecchia et al 5 studied left ventricular structure and function in 346 patients with clinic hypertension and showed a significant increase in left ventricular mass index (LVMI), and in the pattern of mitral blood flow (A/E ratio) in patients with established or persistent hypertension; this was regardless of whether they used their own definition or that of Staessen 2 or O'Brien. 3 The prevalence of echocardiographic left ventricular hypertrophy (LVH) in the patients with established hypertension ranged from 25% to 31% depending on the criteria used.…”
Section: Association With Target Organ Damagementioning
confidence: 99%